2021
DOI: 10.1038/s41557-020-00623-9
|View full text |Cite|
|
Sign up to set email alerts
|

The liberating force of ultrasound

Abstract: The liberating force of ultrasound Sophisticated drug delivery systems are as essential to modern medicine as drugs themselves. Now, polymer mechanochemistry in sonicated solutions has been used to activate drugs in three different systems. These results offer a promising approach that can be tailored to diverse molecular structures of modern pharmaceuticals.revolutionize our approach to the design of new polymers 12 and our fundamental understanding of chemical reactivity 13 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…A US mechanophore breakage (mechanochemical breakage of the polymer reactive units like cyclic rings) can occur in extracts’ solutions via the shear stress caused by the collapse of US-induced cavitation bubbles [ 37 , 38 ]. These modifications in the structure of extracted compounds caused by US can facilitate the bioavailability of the bioactive molecules extracted from plants [ 16 ]. However, the US higher than 50% had a negative effect on the PAs due to the formed radicals and H 2 O 2 by the cavitation’s bubbles [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A US mechanophore breakage (mechanochemical breakage of the polymer reactive units like cyclic rings) can occur in extracts’ solutions via the shear stress caused by the collapse of US-induced cavitation bubbles [ 37 , 38 ]. These modifications in the structure of extracted compounds caused by US can facilitate the bioavailability of the bioactive molecules extracted from plants [ 16 ]. However, the US higher than 50% had a negative effect on the PAs due to the formed radicals and H 2 O 2 by the cavitation’s bubbles [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al [ 21 ] reported that 40 mL/g of S/S was the most efficient solvent concentration, which improved the solubility of PAs in the plant cells. Boulatov [ 16 ] reported that the US mechanochemistry affected overstretching carbohydrates’ polymers that lead to their fragmentation, which helps in releasing small molecules that are bound in their polymer chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside, ones may keep eyes on novel drug liberation mechanism such as mechanochemistry. [252] The detailed mechanism of nanoprodrug assembling remains in its infancy therefore deserve more investigation, in particular the behavior of NPs at fluid-fluid interface. [253] The in situ observation of NPs formation, growth process and trajectory tracking are often technologically challenged and expensive.…”
Section: Remark and Outlookmentioning
confidence: 99%
“…[ 17 ] Recently, we provided the first example of US‐induced mechanochemical bond scission for the activation of drugs, underlining the potential of US for spatial and temporal regulation of medication. [ 18 , 19 ] Furthermore, the combination of nanoparticle systems with polymer mechanochemistry enabled increased drug loading efficiency and enhanced mechanical responses compared to systems relying exclusively on synthetic polymers. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%